2015
DOI: 10.1097/ico.0000000000000393
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Dry Eye and Meibomian Gland Dysfunction With Meibography in Patients With Rosacea

Abstract: Ocular rosacea causes dry eye and significant meibomian gland loss that can objectively be demonstrated with meibography. The infrared camera of OCT-that is widely found in many ophthalmology departments-might be used to evaluate meibomian gland dysfunction in these individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 18 publications
1
28
0
6
Order By: Relevance
“…The meiboscore of individuals with ocular rosacea was found to be significantly higher than that of control subjects, [56][57][58] suggesting that rosacea, a condition with which MGD is often associated, affects the morphology of meibomian glands.…”
Section: Rosaceamentioning
confidence: 91%
“…The meiboscore of individuals with ocular rosacea was found to be significantly higher than that of control subjects, [56][57][58] suggesting that rosacea, a condition with which MGD is often associated, affects the morphology of meibomian glands.…”
Section: Rosaceamentioning
confidence: 91%
“…123 MG dysfunction (MGD), defined by the International Workshop on MGD as a “chronic, diffuse abnormality of the MGs, commonly characterized by terminal duct obstruction and/or qualitative/quantitative changes in the glandular secretion,” is a leading cause of evaporative DED. 1,123125 Recently, imaging of the MGs under infrared illumination has become easier to perform and can be included in clinical trial testing, 126129 but may not be sufficient for diagnosis of MGD or DED. Some studies suggest MG dropout, using direct- or transillumination of the lid, shows a strong relationship between MGD and DED.…”
Section: Point Of Care Biomarkersmentioning
confidence: 99%
“…It was reported that rosacea is accompanied with significant loss of meibomian glands highly associated with eyelid margin inflammation. (Palamar et al, 2015; Machalińska et al, 2016; Liang et al, 2016). Two Demodex species ( folliculorum and brevis ) have been identified as causative mites of rosacea.…”
Section: Dermatological Disorders and Meibomian Gland Pathologymentioning
confidence: 99%